2018
DOI: 10.1167/iovs.18-24534
|View full text |Cite
|
Sign up to set email alerts
|

Matricellular Protein Levels in Aqueous Humor and Surgical Outcomes of Trabeculectomy

Abstract: In previous APAC patients, the SPARC level in aqueous humor is a prognostic factor for surgical results of trabeculectomy. Modulation of SPARC expression may have potential clinical applications after filtration surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Glaucoma surgery serves as a last-resort intervention for patients with uncontrolled IOP. The current study indicated that PSS patients have a higher risk of fibrosis due to the presence of proinflammatory cytokines after trabeculectomy [ 25 , 26 ]. However, in our study, the PSS patients with uncontrolled IOP who received compound trabeculectomy during the attack phase achieved well-controlled postoperative IOP and functional filter blebs.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma surgery serves as a last-resort intervention for patients with uncontrolled IOP. The current study indicated that PSS patients have a higher risk of fibrosis due to the presence of proinflammatory cytokines after trabeculectomy [ 25 , 26 ]. However, in our study, the PSS patients with uncontrolled IOP who received compound trabeculectomy during the attack phase achieved well-controlled postoperative IOP and functional filter blebs.…”
Section: Discussionmentioning
confidence: 99%
“…The two likely mechanisms involved in late surgical failure include the presence of proinflammatory cytokines and fibrosis at the surgical site. [19][20][21][22] Previous studies have shown high levels of proinflammatory Figure 3 Cumulative probability of reoperation for IOP control was greater in the trabeculectomy group compared with the GDD group (P < 0.001, Log rank test). Two eyes had reoperation in eyes with PUC; however, 16 eyes underwent reoperation without PUC.…”
Section: Discussionmentioning
confidence: 99%
“…26 These proinflammatory cytokines are thought to lead to a slow remodeling of extracellular matrix over time leading to a higher risk of surgical failure. 19 In previous studies 9,[27][28][29] which evaluated the success of GDD in UG, different courses of uveitis management were used (Table 4). Factors like preoperative initiation of anti-inflammatory agents, route of medications administered, dosage regimen and duration of perioperative treatment were variable.…”
Section: Discussionmentioning
confidence: 99%
“…However, various factors in the aqueous humor were found rising during acute angle closure, such as matricellular proteins and inflammation factors. The former can cause the extracellular deposition of fibrillary and obstruct the outflow route [ 34 , 35 ], and the latter can cause the function loss of the blebs [ 5 ]. Therefore, we speculated that even though EPO was more elevated to protect the RGCs in severe cases, the level of EPO was not high enough to completely reverse the fibrosis, and it ultimately resulted in surgical failure.…”
Section: Discussionmentioning
confidence: 99%